Antibodies as clinical tools for tuberculosis - McIntyre, Sophie; Warner, Jeffrey; Rush, Catherine; Vanderven, Hillary A. (Frontiers in Immunology, 2023)
Tuberculosis (TB) is a leading cause of morbidity and mortality worldwide. Global research efforts to improve TB control are hindered by insufficient understanding of the role that antibodies play in protective immunity and pathogenesis. This impacts knowledge of rational and optimal vaccine design, appropriate diagnostic biomarkers, and development of therapeutics. Traditional approaches for the prevention and diagnosis of TB may be less efficacious in high prevalence, remote, and resource-poor settings. An improved understanding of the immune response to the causative agent of TB, Mycobacterium tuberculosis (Mtb), will be crucial for developing better vaccines, therapeutics, and diagnostics. While memory CD4+ T cells and IFN-γ have been the main identified correlates of protection in TB, mounting evidence suggests that other types of immunity may also have important roles. TB serology has identified antibodies and functional characteristics that may help diagnose Mtb infection and distinguish between different TB disease states. To date, no serological tests meet the WHO requirements for TB diagnosis, but multiplex assays show promise for improving the sensitivity and specificity of TB serodiagnosis. Monoclonal antibody (mAb) therapies and serum passive infusion studies in murine models of TB have also demonstrated some protective outcomes. However, animal models that better reflect the human immune response to Mtb are necessary to fully assess the clinical utility of antibodybased TB prophylactics and therapeutics. Candidate TB vaccines are not designed to elicit an Mtb-specific antibody response, but evidence suggests BCG and novel TB vaccines may induce protective Mtb antibodies. The potential of the humoral immune response in TB monitoring and control is being investigated and these studies provide important insight into the functional role of antibody-mediated immunity against TB. In this review, we describe the current state of development of antibody-based clinical tools for TB, with a focus on diagnostic, therapeutic, and vaccine-based applications.